Cryptography and network security principles and practice - Stallings, William (Pearson Education Limited, 2017)
The Principles and Practice of Cryptography and Network Security, Stallings' Cryptography and Network Security, Seventh Edition, introduces students to the compelling and evolving field of cryptography and network security. In an age of viruses and hackers, electronic eavesdropping, and electronic fraud on a global scale, security is paramount. The purpose of this book is to provide a practical survey of both the principles and practice of cryptography and network security. In the first part of the book, the basic issues to be addressed by a network security capability are explored by providing a tutorial and survey of cryptography and network security technology. The latter part of the book deals with the practice of network security: practical applications that have been implemented and are in use to provide network security.